An improved gasification kinetic model for biochar with high alkali and alkaline earth metals content. (15th June 2023) - Yi, Wei; Wang, Xianhua; Zeng, Kuo; Yang, Haiping; Shao, Jingai; Zhang, Shihong; Paul Watkinson, A.; Chen, Hanping
Graphical abstract: Highlights: Devolatilization at 350–550 °C significantly increased the K content in corn stalks. K has a more significant catalytic effect on later gasification stage. The fitting accuracy of random pore model decreases with the increase of K content. K content, conversion rate and activity parameter were correlated in improved model. Accurate prediction for gasification of high inorganic content biomass was realized. Abstract: In this study, to investigate the effect of medium temperature devolatilization (MTD) on biomass gasification kinetics and build an improved kinetic model that can accurately describe the gasification of MTD-char, the isothermal steam gasification experiments were performed by using a thermogravimetric analyzer on corn stalk and its MTD-chars obtained at 200–550 °C. The results demonstrate that the wide divergence in the influences of alkali and alkaline earth metal (AAEM) on the gasification under different conversion rates (x) led to the fitting error of the random pore model for corn stalk gasification process, and this fitting error was more significate in the MTD-char with higher AAEMs content. Accordingly, a semi-empirical kinetic model, namely RPM+, which is suitable for biomass gasification with high AAEMs content, especially the MTD-char, was developed, the catalytic effects of AAEMs on biomass gasification were accurately described by the mutual coupling of AAEMs content, x and an activity parameter (ka ) in RPM+. This study is of great significance to the process simulation and equipment design of biomass staged gasification. The results provide the theoretical foundation for realizing the high-value utilization of biomass with high AAEMs content through gasification.